43 Spectrum of pericardial diseases in paediatric population presenting to a tertiary care centre in india. (2nd February 2018) - Saxena, A; Bohra, V; Gupta, SK; Ramakrishnan, S; Juneja, R; Kothari, SS
Abstract : Purpose: There is a paucity of data on acquired pericardial diseases in paediatric population, especially from the developing world. The aim of the study was to define the spectrum and profile of pericardial diseases in Indian paediatric population presenting to a tertiary care centre. Methods: Children 15 years who presented with pericardial disease (based on clinical and echocardiographic parameters) between January 2010 and December 2016 were recruited. Results: A total of 44 patients were enrolled in the study. Their age ranged from 5 months to15 years (mean 6.9±4.8 years), 25 were males. 13 (29.5%) presented with chronic constrictive pericarditis (CCP). The underlying aetiology was tuberculosis in 7 and pyogenic in 3. A total of 24 children had pericardial effusion (PE), cardiac tamponade was present in 4. The aetiology of PE was pyogenic in 11, tubercular in 6 and malignancy in 4. Effusive constrictive pericarditis was seen in 5. Overall tuberculosis was the aetiology in 18 (40.9%) patients. Pericardiocentesis was performed in 27 children, of these 23 had pigtail catheter insertion for drainage. Despite treatment, 60% of patients with tubercular and 45% of patients with purulent PE developed CCP. 18 patients underwent pericardiectomy. Two patients died, one with purulent PE, he died of uncontrolled sepsis and multi-organ failure. The second patient died of low cardiac output following pericardiectomy. Conclusion: In our country tuberculosis still remains as the most common cause of acquired pericardial disease, followed by purulent pericarditis. Many cases progress to constrictive physiology despite treatment, requiring pericardiectomy.